Values clarification as part of shared decision-making with patients with limited health literacy in general practice - Laura Vriese; Jesse Jansen; Bart Knottnerus; Jany Rademakers; Trudy van der Weijden (Health Literacy and Communication Open, 2025)
Background One-third of the Dutch population has limited health literacy (LHL), making it difficult for them to access, understand, appraise, and apply health information. Patients with LHL often adopt a more passive role in shared decision-making (SDM), relying on their doctor to make decisions. A key element of SDM is values clarification: understanding what matters to the patient including their values, preferences, and circumstances. Values clarification remains under-implemented in healthcare settings, despite its relevance to patients with LHL.Aims This study aimed to explore SDM in general practice consultations, focusing on values clarification, as observed by researchers and perceived by general practitioners (GPs) and patients with LHL and multimorbidity.Methods We video-recorded consultations between 20 GPs and 55 patients with LHL and multimorbidity. Subsequently, GPs and patients independently rated perceived SDM using SDM-Q-9. We used OPTION5 to quantitatively measure observed SDM. We qualitatively analyzed how and when values clarification occurred during consultations.Results The observed average SDM performance (OPTION5, range 0–100) was 10.6 (SD 8.2). GPs rated their SDM performance at 64.7, while patients rated it at 88.9 (SDM-Q-9, range 0–100). Qualitative analysis showed that values clarification was about multiple types of preferences, goals, and concerns. GPs typically initiated values clarification by proposing a treatment option and checking if the patient agreed, rather than deliberating collaboratively. This sample of patients with LHL rarely initiated values clarification, but if they did, it mostly occurred early in the consultation when they shared their reason for encounter.Discussion Observed SDM was low. We saw discrepancies between observed and experienced SDM, possibly due to the difference in how instruments measure SDM, or clinicians overestimating their SDM behavior. Patients reported even higher SDM levels than GPs, suggesting differing understandings or social desirability. Shared understanding of the problem seems an important requirement for values clarification. Values clarification was mainly initiated by GPs, but often resembling a paternalistic approach. Asking more open-ended questions may improve values clarification. Future research into perspectives and needs of GPs and patients with LHL could improve values clarification and SDM in general practice.